Porcine meat quallty. Evaluation of technological carcass properties in pig feo thermo process sorghum in the Pampean Semiarid Region (Semiárida, 2020)
Three factors are relevant to consumer's meat quality the tenderness, juiciness and flavor. Objective measurements are related to them as the pH1 and pH24 (1 and 24 hours post mortem), intramuscular lipid content and tenderness, latter as determined by the water asset capacity and cut force of Longissimus dorsi muscle. The pH is associated with tenderness and pH1 (5.5 - 6.3) is generally suitable for fresh meat supply. On the other hand the acidity is linked with quality pork sausage cooked and dry. The purpose of this investigation was to determine whether to process the grain sorghum pressure - high temperature prior to inclusion in the diets of growing and finíshing pigs. can improve carcass quality compared to raw corno The pH of the 1st hour and after 24 hours was significantly different in the control diet of corn relative to sorghum, aspect that determines a meat less water retention in fresh and best resistance to cutting to have less tenderness. Pigs fed sorghum treated exposed carcass best for fresh consumption, for its slow decrease of pH in the first 24 hours, by greater water retention in fresh meat, as measured at water loss by cooking and tenderness of the cut.
Keywords: pig carcass; meat quality; thermo process sorghum